2020
DOI: 10.3389/fmars.2020.00586
|View full text |Cite
|
Sign up to set email alerts
|

The Blue Economy–Cultural Livelihood–Ecosystem Conservation Triangle: The African Experience

Abstract: amalgamates the top-down and bottom-up approaches to BE management. Achieving the goal of successful blue growth in Africa is now even more challenged by the implications of COVID-19 on the BE sectors. Reimagining and rebuilding a resilient BE in Africa post-coronavirus will require a strong political commitment to promoting a balance between economic, social and environmental benefits in line with the African Union's Agenda 2063 and the United Nations' Sustainable Development Goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 111 publications
(125 reference statements)
0
66
0
Order By: Relevance
“…This is of significant concern, particularly as the cumulative effects of multiple noise and ship related stressors remain largely unassessed for the region. WIO states are accelerating plans to diversify marine economies (particularly trade) in keeping with the development of the regional "Blue Economy" (Llewellyn et al, 2016;Okafor-Yarwood et al, 2020). In 2016, there were 13 commercial ports in the WIO region (Celliers and Jackson, 2016) and currently several others are planned, under construction or being expanded (Humphreys et al, 2019).…”
Section: Conservation Issuesmentioning
confidence: 99%
“…This is of significant concern, particularly as the cumulative effects of multiple noise and ship related stressors remain largely unassessed for the region. WIO states are accelerating plans to diversify marine economies (particularly trade) in keeping with the development of the regional "Blue Economy" (Llewellyn et al, 2016;Okafor-Yarwood et al, 2020). In 2016, there were 13 commercial ports in the WIO region (Celliers and Jackson, 2016) and currently several others are planned, under construction or being expanded (Humphreys et al, 2019).…”
Section: Conservation Issuesmentioning
confidence: 99%
“…It is clear, though, that this ideal is frequently not being met and the economic returns of the blue economy do not always benefit local people and when they do, the benefits are frequently inequitably distributed (Bennett, 2018). Three case‐studies from the Pacific Ocean showed failures to achieve integration across stakeholders and to address problems related to power, the agencies involved and gender (Keen et al., 2018) while a review of examples from Africa found that blue economy activities tended to favour economic benefits over environmental sustainability and to exclude local communities (Okafor‐Yarwood et al., 2020). There are also cases where the costs of economic development, for example in the form of wastes and pollution, are born disproportionately by local communities (Bennett, 2018).…”
Section: Developments In Policy and Practices Since 2000mentioning
confidence: 99%
“…The failure to consider and address the benefits and costs for local communities is widely considered to be linked to failures to engage and work with communities in implementation of the blue economy, and also failures to consider gender equity (Bennett, 2018; Jones et al., 2016; Okafor‐Yarwood et al., 2020). Bennett (2018) reports on concerns about increasing capitalization, privatization and enclosure of ocean areas and resources under the name of the blue economy.…”
Section: Developments In Policy and Practices Since 2000mentioning
confidence: 99%
“…mangroves, salt marshes, lagoons, and estuaries), fisheries, tourism, settlements, transport, and industries (e.g. oil, and gas) [ 2 , 11 , 23 , 29 ]. Thirteen of the sixteen West African nations have coastline, and the West African coastline stretches 3480 miles from Mauritania to Nigeria (Fig.…”
Section: Introductionmentioning
confidence: 99%